Pemetaan Potensi Lahan Pertanian Padi Sawah Berdasarkan Indeks Potensi Lahan di Kabupaten Solok Selatan - Putri Wahyuni (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
South Solok Regency is one of the areas that lacks information about the potential of agricultural land in South Solok. The purpose of this study is to map the level of land potential based on the land potential index in South Solok Regency. In this study, it uses tiered quantitative research methods. The quantitative method is a method that uses the provision of values and score calculations in each parameter, this study also uses overlay techniques from several maps for produce information which is then analyzed. The result of the study is the level of land potential based on the land potential index in South Solok Regency is divided into four classes, namely appropriate, very appropriate, less appropriate, and not appropriate. Each with an area of the unsuitable land potential index class covering an area of 348098.6985 Ha, a very suitable paddy field potential index covering an area of 6394.84462 Ha, a suitable paddy field potential index covering an area of 3174.27358 Ha, an unsuitable rice field potential index covering an area of 1551.629185 Ha. The potential level of paddy rice agricultural land based on the land potential index in South Solok Regency has two potential classes, namely appropriate and very appropriate. So the potential area of land suitable for paddy rice farming in South Solok Regency covers an area of 26705,855 Ha.